DC-SIGN Mediates the Interaction Between Neutrophils and Leishmania amazonensis-Infected Dendritic Cells to Promote DC Maturation and Parasite Elimination - Tiburcio, Rafael; Melo, Léon Dimitri; Nunes, Sara; Barbosa, Ana Luísa Augusto; de Oliveira, Elaine Carvalho; Suarez, Martha; Borges, Valéria M.; Tavares, Natalia; Brodskyn, Claudia Ida (Frontiers in Immunology, 2021)
Background Leishmaniasis is a neglected arthropod-borne disease that affects millions of people worldwide. Successful Leishmania infections require the mitigation of immune cell functions leading to parasite survival and proliferation. A large body of evidence highlights the involvement of neutrophils (PMNs) and dendritic cells (DCs) in the establishment of immunological responses against these parasites. However, few studies, contemplate to what extent these cells interact synergistically to constrain Leishmania infection. Objective We sought to investigate how PMNs and infected DCs interact in an in vitro model of Leishmania amazonensis infection. Material and Methods Briefly, human PMNs and DCs were purified from the peripheral blood of healthy donors. Next, PMNs were activated with fibronectin and subsequently co-cultured with L. amazonensis-infected DCs. Results We observed that L. amazonensis-infected DC exhibited lower rates of infection when co-cultivated with either resting or activated PMNs. Surprisingly, we found that the release of neutrophil enzymes was not involved in Leishmania killing. Next, we showed that the interaction between PMNs and infected-DCs was intermediated by DC-SIGN, further suggesting that parasite elimination occurs in a contact-dependent manner. Furthermore, we also observed that TNFα and ROS production was dependent on DC-SIGN-mediated contact, as well as parasite elimination is dependent on TNFα production in the co-culture. Finally, we observed that direct contact between PMNs and DCs are required to restore the expression of DC maturation molecules during L. amazonensis infection. Conclusion Our findings suggest that the engagement of direct contact between PMNs and L. amazonensis-infected DC via DC-SIGN is required for the production of inflammatory mediators with subsequent parasite elimination and DC maturation.